Green process innovations and firm marketing performance in the emerging markets. Issue 4 (16th May 2022) - Mehraj, Danish; Kaur, Simranpreet
Abstract: Green issues have become imperative to business decision‐makers as industries face intensifying public sensitivity, stricter regulation, and mounting stakeholder pressures engrossed in preserving the natural environment. This increasing pressure is forcing businesses to the adoption of green marketing practices. In an attempt to revisit present‐day severe environmental issues, this paper studies the significant role of green process innovation in the Indian context. Data was collected from 400 manufacturing firms and was analyzed using the appropriate statistical tools to validate the model. The results suggest green process innovation plays a significant role in the relationship between green marketing practices and firm market performance. The findings contribute to the theory of the green marketing concept. Since this study's results expand the existing literature on the adoption of green marketing practices, valuable insights can be endowed to businesses and regulators for preserving the natural environment by considering green process innovation. Further, it offers wide‐ranging implications for managers, marketers and policymakers, which can help them improve their business operations and provide them with a competitive advantage over their competitors.